Communicating trustworthiness in online stores - Kaukoranta, Annika (My University, 2014)
Even though e-commerce systems are expected to have many advantages compared to the traditional ways of doing business, it is not always the reality. Lack of trust is still said to be one of the most important barriers to online shopping. In traditional stores, trust has usually been established in a direct contact between the customer and the company or its personnel. In online stores, there is no direct interaction. The purpose of this thesis is to identify the key antecedents to online trust and to distinguish between effective and ineffective practices. A model on how consumers establish initial trust towards an unknown online vendor was proposed based on previous theories. The model was tested empirically by targeting an online survey at higher degree students in Finland and in Germany. The data confirmed the proposed view that trusting intentions are affected by individual characteristics, characteristics of the company as well as characteristics of the website. Additionally national differences were found between Finnish and German respondents. The data suggested that online vendors can convey a message of trustworthiness by improving information quality and overall usefulness of the website. Perceived risk of online shopping was found to depend especially on general trust in the Internet, service quality and ease of use. A trustworthy online store should include several payment methods as well as means to access and modify given data. The vendors should also make sure that inquiries are addressed quickly, transactions are confirmed automatically and that customers have a possibility to track their order. A model that includes three different sources of trust should contribute to the theoretical understanding of trust formation in online stores. The resulting list of trust antecedents can also be used as a checklist when e-commerce practitioners wish to optimize the trust building.